Investigation of the physical-mechanical properties and durability of high-strength concrete with recycled PET as a partial replacement for fine aggregates - Qaidi, Shaker; Al-Kamaki, Yaman; Hakeem, Ibrahim; Dulaimi, Anmar F.; Özkılıç, Yasin; Sabri, Mohanad; Sergeev, Vitaly (Frontiers in Materials, 2023)
In this study, PET plastic waste, which is a type of polymer commonly used in the manufacture of plastic bottles, has been incorporated into concrete by partially replacing the natural fine aggregate. An experimental study was conducted by casting and testing 90 concrete cylinders and 54 concrete cubes. A concrete mixture was designed in which the natural fine aggregate was substituted partially with PET plastic waste (PW) at a ratio of 0%, 25%, and 50%, with various w/c ratios of 0.40, 0.45, and 0.55. Physical, mechanical, and durability properties were assessed. The downside of the test results show degradation in each of the following characteristics: slump, compressive strength, splitting tensile strength, ultrasonic pulse velocity, water absorption, and porosity. The degradation of these characteristics increased with the increase in the volume of plastic aggregate (PA) and the w/c ratio. While the positive side of the results showed that with the increase of the PA volume and the w/c ratio, the fresh and dry densities decreased further, and by using 50% PET, the dry density became below 2000 kg/m3. Therefore, it is classified as lightweight concrete. Moreover, the fracture of concrete changed from brittle to more ductile compared to control concrete. Also, the thermal conductivity decreased significantly (11-47%), and by using 50% of PET, the thermal conductivity became less than 0.71 W/mK, and accordingly, classified as a bearing insulator.